2016
DOI: 10.3390/ijms17030319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression Analysis of Eight PgWRKY Genes in Panax ginseng Responsive to Salt and Hormones

Abstract: Despite the importance of WRKY genes in plant physiological processes, little is known about their roles in Panax ginseng C.A. Meyer. Forty-eight unigenes on this species were previously reported as WRKY transcripts using the next-generation sequencing (NGS) technology. Subsequently, one gene that encodes PgWRKY1 protein belonging to subgroup II-d was cloned and functionally characterized. In this study, eight WRKY genes from the NGS-based transcriptome sequencing dataset designated as PgWRKY2-9 have been clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…It has been noted that increased activation of some genes and the biosynthesis of specific proteins may improve the adaptation of the plant to drought or salt-stress conditions. For example, in Panax sp., the expression of S-adenosyl-L-methionine synthetase, PgWRKY1,2,4,5,8,9, LHT-type plant amino acid-transporter, and MYB transcription factor is activated in response to ABA treatment [16,17,18,19,20]. Literature data also indicates that abscisic acid can regulate the biosynthesis of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that increased activation of some genes and the biosynthesis of specific proteins may improve the adaptation of the plant to drought or salt-stress conditions. For example, in Panax sp., the expression of S-adenosyl-L-methionine synthetase, PgWRKY1,2,4,5,8,9, LHT-type plant amino acid-transporter, and MYB transcription factor is activated in response to ABA treatment [16,17,18,19,20]. Literature data also indicates that abscisic acid can regulate the biosynthesis of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Nuruzzaman et al. obtained 48 transcription factors related to the ginsenoside synthesis by transcriptional sequencing of the adventitious roots treated with MJ, in which the transcription factors of WRKY1‐9 were identified. In addition, it was found that WRKY1‐9 had different expression levels in roots, stems, leaves, adventitious roots, and seeds.…”
Section: Regulation Of Ginsenoside Biosynthetic Pathwaymentioning
confidence: 99%
“…Some genes, including WRKY transcription factors (TFs), are induced to help plants adapt to stresses by changing physiology and morphology. WRKY TFs were a valuable family which resisted abiotic stress, such as cold, NaCl, drought, salicylic acid, ethylene, abscisic acid, methyl jasmonate, and hydrogen peroxide (H 2 O 2 ) (Wang et al, 2013;Zhou et al, 2015;Xiu et al, 2016). The WRKY family comprised one or two DNA-binding domains consisted of 60 amino acid regions and the highly conservative sequence WRKYGQK at its N-terminus and a zinc-finger motif (Cx 4−5 Cx 22−23 HxH or Cx 7 Cx 23 HxC) at C-terminus (Eulgem et al, 2000;Rushton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%